2004
DOI: 10.1677/joe.0.1810271
|View full text |Cite
|
Sign up to set email alerts
|

GH and insulin affect fatty acid synthase activity in isolated porcine adipocytes in culture without any modifications of sterol regulatory element binding protein-1 expression

Abstract: The ability of GH to decrease fatness and insulin-regulated events such as lipogenic enzyme activities is well known in pigs. Nevertheless, the precise mechanism underlying these actions has not been elucidated yet. Expression of the transcription factor sterol regulatory element binding protein (SREBP)-1 has been reported as a key mediator of insulin action in rat hepatocytes and adipose cell lines. The present study aimed to determine whether the regulation of lipogenesis by GH and/or insulin in porcine adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
7
17
0
Order By: Relevance
“…A similar decrease in the enzymatic activity has been observed in cultures of adipose tissue explants (Lanna et al, 1994) and also in isolated adipocytes cultured for 48 h (Louveau and Gondret, 2004). However, the magnitude of the reduction in activity was smaller than that observed with swine adipose tissue explants biopsied after 1 to 4 weeks of in vivo treatment with pGH, which showed a 40 to 80% reduction in FAS activity (Harris et al, 1993;Donkin et al, 1996a;Lee et al, 2000).…”
Section: Growth Hormone Effects On Fas Activitysupporting
confidence: 75%
See 2 more Smart Citations
“…A similar decrease in the enzymatic activity has been observed in cultures of adipose tissue explants (Lanna et al, 1994) and also in isolated adipocytes cultured for 48 h (Louveau and Gondret, 2004). However, the magnitude of the reduction in activity was smaller than that observed with swine adipose tissue explants biopsied after 1 to 4 weeks of in vivo treatment with pGH, which showed a 40 to 80% reduction in FAS activity (Harris et al, 1993;Donkin et al, 1996a;Lee et al, 2000).…”
Section: Growth Hormone Effects On Fas Activitysupporting
confidence: 75%
“…It is indeed possible that the pGH might only act indirectly through modulation of the insulin-signaling cascade. The mechanism by which growth hormone interferes with the action of insulin on FAS gene transcription has not yet been totally elucidated (Louveau and Gondret, 2004). Magri et al (1990) observed that a decrease in insulin sensibility caused by growth hormone in swine adipose tissue was neither associated with changes in the number of insulin receptors nor in tyrosine kinases activity.…”
Section: Effect Of Growth Hormone On Fas Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SREBP-1c, it was not clear whether the increase in FAS activity was the result of a direct effect of insulin on the adipocytes or the result of a transactivation of the FAS promoter, inducing a further increase in the FAS activity in these cells. However, a recent study showed that no change in SREBP-1 mRNA levels was observed in response to insulin in porcine adipocytes ( I Louveau et al 2004). The report differs from results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, its production was found not only in the hypothalamus, but also in other parts of the nervous system and organs in the digestive tract. The GH for a long time been investigated as an anabolic hormone that regulates the metabolism, stimulates growth and overall body weight, promotes tissue regeneration and cell survival (Louveau and Gondret, 2004). Synthesis and secretion of GH is controlled somatoliberin hypothalamic hormones and somatostatin.…”
Section: Introductionmentioning
confidence: 99%